A General and Practical Approach for the Synthesis of 1, 2, 4‐Trioxanes Catalyzed by Silica‐Ferric Chloride. Issue 20 (6th September 2017) - Zhang, Mo; Han, Yi; Niu, Jia‐Liang; Zhang, Zhan‐Hui
Abstract: An efficient and practical method has been developed for the facile synthesis of 1, 2, 4‐trioxanes by the condensation of β‐hydroperoxy alcohols and carbonyl compounds in the presence of a catalytic amount of silica‐supported ferric chloride (FeCl3 /SiO2 ) at room temperature. The method has the benefits of operational simplicity, high yields and potential large‐scale application. Moreover, the catalyst can be readily recovered by simple filtration and reused up to five times while almost maintaining its catalytic activity. Abstract :